More than a politician of Independence: scientist José Bonifácio de Andrada e Silva (Research, Society and Development, 2022)
The scientist and intellectual José Bonifácio de Andrada e Silva (1763-1838) is, certainly, best known in Brazil for his political action, especially for issues related to the Independence of Brazil. However, during the long period he lived in Portugal, José Bonifácio was one of the most active scientists of his time, with enormous influence also in political and economic matters. Bonifácio José de Andrada, José Bonifácio’s father, was a family member of the Portuguese aristocracy in the city of Santos (São Paulo) and had the second biggest fortune in the city, while José Ribeiro de Andrada, his grandfather, was related to the aristocrats of his land, belonging to an old Portuguese family. He moved to São Paulo at the age of fourteen, where he attended classes in Grammar, Rhetoric, Philosophy and where he did the preparatory education to enter the University of Coimbra, a place where resourceful Brazilians went, and which would transform him into a great naturalist (scientist). We intend to explain that his work as a scientist went far beyond what the simple title of “Patriarch” of the Brazilian nation teaches us in school benches, having even discovered new minerals and becoming the first geologist in the Americas.